Answer:
The distance from vertex B to the midpoint of AC is 3.
Step-by-step explanation:
From Linear Algebra we understand that location of the midpoint of AC is determined by the following formula:
[tex]M(x,y) = \frac{1}{2}\cdot A(x,y) + \frac{1}{2}\cdot C(x,y)[/tex] (1)
Where:
[tex]A(x,y)[/tex], [tex]C(x,y)[/tex] - Locations of vertices A and C regarding origin, dimensionless.
[tex]M(x,y)[/tex] - Location of the midpoint regarding origin, dimensionless.
If we know that [tex]A(x,y) = (1,-3)[/tex] and [tex]C(x,y) = (5,-3)[/tex], then the midpoint of AC is:
[tex]M(x,y) = \frac{1}{2}\cdot (1,-3)+\frac{1}{2}\cdot (5,-3)[/tex]
[tex]M(x,y) = \left(\frac{1}{2},-\frac{3}{2} \right)+\left(\frac{5}{2}, -\frac{3}{2} \right)[/tex]
[tex]M(x,y) = (3, -3)[/tex]
Lastly, the distance from vertex B to the midpoint of AC is calculated from the Pythagorean Theorem:
[tex]d = \sqrt{(M_{x}-B_{x})^{2}+(M_{y}-B_{y})^{2}}[/tex] (2)
If we know that [tex]M_{x} = 3[/tex], [tex]M_{y} = -3[/tex], [tex]B_{x} = 3[/tex] and [tex]B_{y} = 0[/tex], then the distance is:
[tex]d = \sqrt{(3-3)^{2}+(-3-0)^{2}}[/tex]
[tex]d = 3[/tex]
The distance from vertex B to the midpoint of AC is 3.